Analysis of the need to create a model of Muara Takus Temple using the green history approach as a medium for learning history - Rizki Ananda Hasibuan; Yanuar Al-fiqri; Bunari Bunari; Yuliantoro Yuliantoro (Universitas Negeri Malang, 2026)
This study aims to conduct a needs analysis for developing a Muara Takus Temple model based on the Green History approach as an innovative medium for history learning. The research employed a qualitative descriptive design with a case study approach conducted at SMAN 12 Pekanbaru. Participants consisted of 1 history teacher and 32 eleventh-grade students selected through purposive sampling. Data were collected through classroom observations, semi-structured interviews, and documentation analysis, and were analyzed using an interactive model involving data reduction, data display, and conclusion drawing. Data validity was ensured through triangulation of sources and techniques. The findings reveal three main results. First, existing history learning practices are still dominated by lecture-based methods with limited use of interactive media, resulting in low student engagement and superficial understanding of local historical content. Second, both teachers and students expressed a strong need for visual, contextual, and environmentally oriented learning media, particularly for complex historical topics such as Muara Takus Temple. Third, the proposed model made from recycled materials has the potential to enhance students’ conceptual understanding, learning motivation, and environmental awareness, although challenges related to technical production and teacher readiness remain significant. This study concludes that the development of a Green History–based temple model is pedagogically relevant and urgently needed, as it integrates historical understanding with sustainability values. The study recommends systematic development, teacher training, and institutional support to ensure effective and sustainable implementation in history learning.